Implementasi Manajemen Strategik Program Pendidikan Dan Latihan Kebijakan Revolusi Mental - Kapitan Kelibai; Suryadi -; Bedjo Sujanto (Jurnal Ilmiah Wahana Pendidikan, 2018)
This study aims to determine and mean descriptively the implementation of strategic management of educational programs and the training of mental revolution policies. Data collection methods that are owned are through observation, interviews, field notes and documents that can be accounted for. Data analysis method is carried out data analysis techniques obtained through the type of research both through secondary data and primary data, then analyzed descriptively and conclusively concluded. Data analysis includes testing, grouping and testing or collecting data / evidence to draw research results in the form of descriptions written in narratives to complete the overall picture. The results of the study found in this study are mental revolution education and training have a strategic, practical, and massive management system to improve the way of thinking, ways of working and ways of life for Praja Pioneers of the Mental Revolution (PPRM), the Pioneer of the Mental Revolution (KPRM) and the Revolutionary Mental Revolutionary Apparatus (APRM). The findings of this study are the implementation of education and mental revolution training there are two educational processes in it, namely formal education and informal education. The goal is the value of the mental revolution can change the character and character or mental of the apparatus and also understand strategic management (Planning, Implementation and Monitoring / Evaluation).